Efficacy and safety comparison of nabpaclitaxel plus S-1 and gemcitabine plus S-1 as first-line chemotherapy for metastatic pancreatic cancer. (28th April 2018) - Xu, Yaolin; Guo, Xi; Fan, Yue; Wang, Dansong; Wu, Wenchuan; Wu, Lili; Liu, Tianshu; Xu, Bei; Feng, Yi; Wang, Yan; Lou, Wenhui; Zhou, Yuhong
Abstract : For metastatic pancreatic cancer, Nabpaclitaxel & S-1 provided more benefits (time to progression 7.1 vs. 3.6 months; overall survival 10.2 vs. 6 months) compared with Gemcitabine & S-1. Abstract: Objective: To compare efficacy and safety of nabpaclitaxel plus S-1 (AS) with gemcitabine plus S-1 (GS) as first-line treatment for metastatic pancreatic cancer. Methods: We conducted a retrospective cohort, single-institution analysis by reviewing medical records of 38 patients who received either AS (nabpaclitaxel 125 mg/m 2 on Days 1, 8 and S-1 80 mg/m 2 on Days 1 to 14) or GS (gemcitabine 1000 mg/m 2 on Days 1, 8 and S-1 80 mg/m 2 on Days 1 to 14) chemotherapy. Results: AS was associated with a prolonged median time to progression (TTP; 7.1 months, 95% CI, 4.5–9.7 vs. 3.6 months, 95% CI, 1.8–5.4; P value = 0.022) and improved median overall survival (OS; 10.2 months, 95% CI, 9.1–11.3 vs. 6 months, 95% CI, 4.2–7.8; P value <0.001) compared with GS. In cox proportional hazards model, treatment regimen was the only variable to be significantly associated with improvements in both TTP and OS. Subgroup analyses based on HER2 expression showed that AS seemed to have better outcome of OS in HER2 positive patients (HR = 0.168; 95% CI, 0.022–1.27; P value = 0.084). Hematological adverse events were commonly seen in both group (12.5% and 22.7%, GS and AS group, Grade 3 or 4; P value = 0.675) while AS got increased risk of sensory neuropathy (6 of 22 patients in AS, 27.3% vs. 0 of 16 patients in GS, all grade; P value = 0.03). Conclusions: AS could be an effective treatment regimen for metastatic pancreatic cancer under surveillance of toxicity.